Response of okra seed crop to sowing time and plant spacing in south eastern hilly region of Bangladesh (Bangladesh Journal of Agricultural Research, 2008)
A field experiment on okra cv. BARI Dherosh1 comprising four sowing times starting from February to May (15th day of each month) at monthly interval and four spacings (60 × 30, 60 × 40, 60 × 50, and 60 × 60 cm) was conducted at the Agricultural Research Station (ARS), Raikhali, Rangamati Hill District to find out the most suitable sowing time and optimum plant spacing for the two consecutive years of 1997 and 1998. The highest seed yield (2.97 t/ha) was recorded from 15 April sowing closely followed by 15 March sowing (2.77 t/ha) whereas the best quality seed was obtained from 16 February (88.7% germination and 29.75 seed vigour index) and 15 March (83.7% germination and 28.80 seed vigour index) sowing. Plant spacing of 60 × 40 cm produced the highest seed yield of okra (2.86 t/ha) followed by 60 × 30 cm spacing (2.80 t/ha). The germination percentage and seed vigour index were unaffected due to different plant spacings. 15 April sowing accompanied with 60 × 30 cm spacing gave the highest seed yield (3.13 t/ha) closely followed by 60 × 30 cm spacing with the same sowing time (3.06 t/ha). The seed yield did not decline in 15 March sowing having similar spacings.DOI: http://dx.doi.org/10.3329/bjar.v32i3.541Bangladesh J. Agril. Res. 32(3) : 393-402, September 2007